THE RELATIONSHIP BETWEEN KNOWLEDGE AND MOTHERS’ WORK REGARDING BREAST MILK STORAGE IN THE WORKING, FAKFAK DISTRICT, WEST PAPUA PROVINCE IN 2024 - Jumriana; Putri, Ninsah Mandala; bakti rajagukguk, kezia s.a; Destri Sakina Selian; Hutapea, Perdana Tiares (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background Exclusive breastfeeding is the most appropriate source of nutrition for infants and contributes significantly to improving child health and survival. However, working mothers often experience difficulties in maintaining exclusive breastfeeding because of limited time with their infants. Expressing and storing breast milk is a practical solution that enables continued breastfeeding during maternal absence. The successful implementation of this practice depends largely on mothers’ knowledge of correct breast milk storage procedures. Objective This study aimed to examine the relationship between maternal knowledge and breast milk storage practices among working mothers. Methods A descriptive-analytic study with a cross-sectional design was conducted among 32 pregnant and breastfeeding mothers. The respondents were selected using a total sampling technique. Data were collected through a structured online questionnaire and analyzed using univariate and bivariate statistical methods. The association between maternal knowledge and breast milk storage practices was assessed using the Spearman Rank correlation test with a significance level of 0.05. Results The findings indicated that 45.1% of respondents had limited knowledge regarding breast milk storage. Meanwhile, 51.6% demonstrated appropriate breast milk storage practices. The statistical analysis showed a significant relationship between maternal knowledge and breast milk storage practices (p = 0.000). Mothers with a better understanding of breast milk management were more likely to apply proper storage procedures. Conclusion Maternal knowledge is an important factor influencing breast milk storage practices among working mothers. Enhancing knowledge through breastfeeding education, counseling, and workplace support programs may improve breast milk handling practices and contribute to the achievement of exclusive breastfeeding.